Cash Flow Management Practices and Financial Performance of Non-Financial Firms Listed in the Nairobi Securities Exchange - Chepkoech, Daisy; Miroga, Julius (International Journal of Finance, 2025)
Purpose: This study seeks to assess the relationship between cash flow management practices and Financial Performance of non-financial Companies Listed at Nairobi Security Exchange. The study mainly focused on assessing the effect of investing cash flows, effect of operating cash flows and to evaluate the effect of financing cash flows, and the effect of cash flow analysis on Financial Performance of non-financial Companies Listed at Nairobi Security Exchange. The study was guided by free cash flow theory, agency cost theory and Keynesian theory of money. Methodology: Cross sectional research design was adopted and all 44 companies listed at NSE in the year 2017 to 2023 were used to form a sample size. Annual financial reports and other financial statements between the periods 2017-2023 were used to provide secondary data. Data was analyzed by the help of STATA software. Descriptive and inferential statistics were used in data analysis. Findings: The findings revealed that operating cash flows positively influence financial performance, while investing and financing cash flows have negative effects, indicating inefficiencies in investment decisions and excessive reliance on external financing. The study concludes that effective management of operating cash flows enhances firm performance, whereas poor investment and financing decisions may hinder financial stability. Unique Contribution to Theory, Practice and Policy: The findings may be significant to various companies’ management, financial policy makers, government in determining tax performance of the companies and lastly this may provide literature for researchers and scholars. It is recommended that firms adopt sound working capital policies, optimize capital investment strategies, and maintain an optimal financing structure to enhance liquidity and profitability. Further research could explore industry-specific cash flow dynamics and the role of financial technology in cash flow management.